“Nāpāk Jism”: Vampirism as Queer Desire in Khwaja Sarfraz’s Zinda Laash (1967) - Dr. Khurshid Alam*, Syeda Momina Masood* & (Journal of Research in Humanities, 2020)
This paper will study Khwaja Sarfraz’s, Zinda Laash (1967), from a queer theoretical paradigm to explore the film’s representation of queer masculinity and womanhood. Zinda Laash is the story of a vampire who infects his victim with non-heterosexual desire, and thus the threat posed by the film’s vampire protagonist, Tabani, is the dismantling of heteronormativity. Based on Bram Stoker’s Dracula (1897), Zinda Laash imagines the figure of the vampire as a queer threat, and the purpose of this paperisto explore queerrepresentation and queer desire in the film. Tabani’s infection of his victims enables them to desire beyond the confines of heterosexuality, and allows them to subvert heteropatriarchal structures of marriage and family, by imagining counter- normative ways of being, belonging, and expressing intimacy and desire. Zinda Laash, as Pakistan’s first horror film, places the element of danger and horror in the queer vampire body and through a queer theoretical study of this film, we will argue that queerness on the Pakistani cinematic screen has been represented as essentially monstrous and represents social anxieties regarding anti- normative gender performances and sexual identities.